Secondary School Heads’ Technology Leadership Skills, Educational Motivation, Teachers’ Techno-Pedagogical Competence in the City Schools Division of Laguna - Lambot, George V.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Techno-pedagogical competency is the hybrid method of educating wherein ICT is applied for teaching learning situations. It is one of the skills of the teachers to effectively integrate technology and pedagogy in the classroom. The goal of this study was to ascertain the secondary school heads’ technology leadership skills, educational motivation, and teachers’ techno-pedagogical competence in the Schools Division of Laguna. Likewise, it explored the relationship between the respondents’ level of secondary school heads’ technology leadership skills and level of educational motivation, level of secondary school heads’ technology leadership skills and level of teachers’ techno-pedagogical competency, and level of secondary school heads’ educational motivation and level of teachers’ techno-pedagogical competency as well as the predictive ability of the level of secondary school heads’ technology leadership skills, and level of educational motivation taken singly or in combination, of level of techno-pedagogical competence. Findings revealed that there was a multiple correlation between the level of secondary school heads’ technology leadership skills, and level of educational motivation taken singly or in combination, of level of techno-pedagogical competency. A value of 0.000 indicated a high level of prediction of the dependent variable (Techno-Pedagogical Competency). The obtained R square of 0.443 showed that independent variables (level of secondary school heads’ technology leadership skills and level of educational motivation) explain the variability of the dependent variable (Techno-Pedagogical Competency).